Clinical guideline for the diagnosis and treatment of cutaneous warts (2022). Issue 3 (18th September 2022) - Zhu, Peiyao; Qi, Rui‐Qun; Yang, Yang; Huo, Wei; Zhang, Yuqing; He, Li; Wang, Gang; Xu, Jinhua; Zhang, Furen; Yang, Rongya; Tu, Ping; Ma, Lin; et al.
Abstract: Aim: Cutaneous warts caused by human papillomavirus are benign proliferative lesions that occur at any ages in human lives. Updated, comprehensive and systematic evidence‐based guidelines to guide clinical practice are urgently needed. Methods: We collaborated with multidisciplinary experts to formulate this guideline based on evidences of already published literature, focusing on 13 clinical questions elected by a panel of experts. We adopted Grading of Recommendations Assessment, Development and Evaluation (GRADE) system to form classification of recommendations as well as the improved Delphi method to retain respective recommendations with a consensus degree of over 80%. Results: Our guideline covered aspects of the diagnosis and treatment of cutaneous warts such as diagnostic gold standard, transmission routes, laboratory tests, treatment principle, clinical cure criterion, definitions, and treatments of common warts, flat warts, plantar warts, condyloma acuminatum, and epidermodysplasia verruciformis. Recommendations about special population such as children and pregnant women are also listed. In total, 49 recommendations have been obtained. Conclusions: It is a comprehensive and systematic evidence‐based guideline and we hope this guideline could systematically and effectively guide the clinical practice of cutaneous warts and improve the overall levels of medical services.